Involution of the Wolffian duct in the rat - Jirsová, Z; Vernerová, Z (Functional and developmental morphology, 1993)
The involution of Wolffian duct in female rat fetuses from 15 to 21 days of gestation was studied in electron microscope. The female Wolffian duct stopped its differentiation on day 17 and the onset of duct regression was found in 18 days old fetuses. The involution was accompanied by degeneration and disintegration of epithelial cells, removal of basal lamina and elimination of altered cells into periductal mesenchyme. Although the mechanism of programmed cell death contributed to the WD regression the findings of non-altered epithelial cells supported the opinion of possible migration of some WD cells into the mesenchymal cell compartment.
Keywords: krysa rodu Rattus; Animals; Sex Differentiation; Wolffovy vývody; Female; zvířata; Wolffian Ducts; sexuální diferenciace; Rats, Wistar; Rats; Microscopy, Electron; ženské pohlaví; potkani Wistar; elektronová mikroskopie